Bakti Sosial Peduli Korban Kebakaran Sape Oleh Civitas Akademika Sekolah Tinggi Ilmu Ekonomi (STIE) Bima - PUji Muniarty; Wulandari Wulandari; Mawar Hidayati (Edumedia Solution, 2022)
The Community Service Team of the Bima College of Economics (STIE) is a collection of the academic community consisting of leaders, lecturers, staff and campus security who care about the condition of the community. STIE Bima cares about the Sape Naru fire as a place to channel ideas and contributions, wants to contribute in the form of social service that is felt directly by the community. Social service is an alternative solution to the problems of today's society. The social service activity was carried out in the fire area in Naru Hamlet, Sape District, Bima Regency, NTB. The stages of service activities include preliminary studies, preparation, distribution, and activity reports. The purpose of social service, apart from being a community activity, is also to raise awareness for sharing which needs to be further improved so that care for the surrounding environment is maintained. All donations in the form of mats, proper clothes, medicines, basic necessities and cooking needs were recorded by type and amount. The distribution of aid is divided into three points, namely, the main post which is directly adjacent to the refugee camp, the post near the main road and the post in the Sape sub-district. In the distribution stage or distribution of basic food packages, lecturers and staff use a participatory approach. Based on community service in the form of distributing basic necessities at the fire site, Naru Hamlet, Sape District, Bima Regency, it showed a positive impact on fire victims.